Perbedaan pola tanam dan kriteria aplikasi insektisida memengaruhi keanekaragaman arthropoda tanah pada pertanaman kubis (Brassica oleracea) - Inrianti Sari Handayani; Dadang Hermana; Ali Nurmansyah (Jurnal Entomologi Indonesia, 2019)
The use of intensive and excessive insecticides on cabbage cultivations causes pest resistance, pest resurgence, environmental pollution, chemical residues, as well as decreasing the population of natural enemies and soil arthropods. Various pest control techniques have been developed to reduce the pest population, two of them are intercropping systems as part of cultural technique strategy and insecticide application. The aim of this research was to study the effect of three cabbage (Brassica oleracea) cultivation patterns and different criteria in insecticide application against soil arthropod diversity including the natural enemy population. The research was designed using split-plot experimental design. The three cultivation patterns consisted of intercropping cabbage with tomato, cabbage, and Ageratum sp. as refugia plant, and monoculture cabbage. Three criteria in insecticide application were economic threshold-based application, calendar system, and without insecticide application. In general, the results showed that cabbage monoculture cultivation and insecticide applications resulted in the lowest soil arthropod population among other treatments. Treatments of cabbage and Ageratum sp. and without insecticide application could increase the diversity of soil arthropods.